Staphylococcus Aureus Osteomyelitis as an Inducer of Tolerance to Escherichia Coli Pyelonephritis: an Experimental Study - Goumenos, Stavros (Sci Rep, 2020)
The high incidence of osteomyelitis in vulnerable populations like those with multiple injuries or elderly undergoing joint arthroplasties generates the question what may be their responses to subsequent infection by high virulent isolates. Rabbits were subject to two operations at three week intervals; sham osteomyelitis and sham pyelonephritis (group S); sham osteomyelitis and Escherichia coli pyelonephritis (group P); and Staphylococcus aureus osteomyelitis and E. coli pyelonephritis (group OP). Survival was recorded; cytokine stimulation of circulating mononuclear cells (PBMCs) and tissue myeloperoxidase (MPO) activity and bacterial growth were monitored. In some experiments, dalbavancin treatment was given before pyelonephritis. Healthy PBMCs were pre-treated with bone homogenate, S. aureus or both. Mortality of groups S, P and OP after induction of pyelonephritis was 0%, 50% and 8.3% respectively. Tumour necrosis factor-alpha (TNFα) production by PBMCs was significantly lower in the OP group at 48 hours. E. coli bacterial load was similar in groups P and OP at death or sacrifice whereas the MPO activity of group OP was decreased. Production of TNFα was further decreased among dalbavancin treated rabbits; in these rabbits tissue MPO was increased. TNFα production decreased when healthy PBMCs pre-treated with bone homogenate, S. aureus (HKSA) or both were stimulated with E. coli (HKEC); production was further decreased in the presence of anti-TLR4 and anti-TLR9. It is concluded that staphylococcal osteomyelitis modulated the innate immune responses of the host leading to protection from death by highly virulent E. coli. Tolerance to TLR ligands is the most likely mechanism of action.